THE RECURRENT APPROACH TO RISK MANAGEMENT IN INNOVATIVE ACTIVITY - G. Brega (Управленческие науки, 2015)
The implementation of the innovative project is practically always associated with increased risk. Under modern conditions of increasing uncertainty in economic and other social processes the need for seeking techniques, methodsand technologies of risk management objectively increases, which leads to shifting to new risk-oriented approaches. The currency of the chosen topic is due to the controversy in methodology issues, on the one hand, and insufficient studies of technologies and principles of risk management in innovation, on the other hand.The article considers a conceptual model of risk management in the formation and realization of the innovative project. It is based on a matrix system of risk analysis. This model is determined by a combination of the following requirements: the regard for the range of risk temporal boundaries; the determination of the zone of economic stability; the hierarchical character of the risk management model; the consistency in building risk management model; the determination of major groups and subgroups of resources; the determination of expected or desired results. The article describes the features of each stage and, in addition, offers the characteristic of technological, legal, social, informational, organizational factors.According to the author, the process of risk management in innovation should be built on the basis of the recurrent approach. It is based on the ability of the organization to a permanent modifi ation of the complex methods of risk management throughout the entire innovation project. In other words, the recurrent approach implies a continuous«recurrence» to the various stages of risk management in order to better adjust the organization to internal and external environmental changes. Special attention is paid to the conditions and factors of the recurrent approach implementation in innovation project risk management.The recurrent approach to innovation project risk management, according to the author, provides for increasing the efficiency of decision making process in the implementation and development of innovations.